The multifunctionality of ruderal ecosystems is highly resistant to climate change - Rocío Rodríguez; Antonio Gallardo; Luis Villagarcia; Guiyao Zhou; Tadeo Sáez-Sandino; Samuel Castejón; Ana López; Jesús G. P. Rodríguez; Felipe Bastida; Manuel Delgado-Baquerizo (Plant and Soil, 2026)
Background and aim The global-scale abandonment of rural areas is resulting in a mosaic of disturbed ecosystems dominated by ruderal vegetation. Yet, the impacts of climate change on the functioning of ruderal ecosystems remain virtually unknown. Methods We conducted a 4-year field experiment to evaluate, for the first time, the long-term impacts of warming and rainfall reduction on the capacity of a ruderal Mediterranean ecosystem to maintain multiple ecosystem services. Results We found that, in general, ruderal ecosystems are highly resistant to climate change with minor effects of warming and rainfall reductions on plant biodiversity and multiple ecosystem services. In fact, we detected small but positive impacts of climate change on certain individual services, with warming enhancing primary production and soil carbon stocks, whereas the combined effects of warming and rainfall exclusion significantly reduced soil carbon stocks. Variation partitioning analysis further revealed that climate accounted for the largest share of variation in both primary production and soil carbon stocks. Conclusions Our results highlight the complexity of climate change interactions in explaining the capacity of ruderal ecosystems to support multiple ecosystem services, and further highlight the overall resistance of these already disturbed ecosystems to climate change.